Essays on antisemitism, anti-Zionism, and the left - Améry, Jean 1912-1978 (Studies in antisemitism, 2021)
"In April 1945, Jean Améry was liberated from the Bergen Belsen concentration camp. A Jewish and political prisoner, he had been brutally tortured by the Nazis, and had also survived both Auschwitz and other infamous camps. His experiences during the Holocaust were made famous by his book At the Mind's Limits: Contemplations by a Survivor of Auschwitz and Its Realities. Essays on Antisemitism, Anti-Zionism, and the Left features a collection of essays by Améry translated into English for the first time. Although written between 1966 and 1978, Améry's insights remain fresh and contemporary, and showcase the power of his thought. Originally written when leftwing antisemitism was first on the rise, Améry's searing prose interrogates the relationship between anti-Zionism and antisemitism and challenges the international left to confront its failure to think critically and reflectively"--